Critical Review of European Health-Economic Guidelines for the Health Technology Assessment of Medical Devices - Blüher, Maximilian; Saunders, Sita J.; Mittard, Virginie; Torrejon Torres, Rafael; Davis, Jason A.; Saunders, Rhodri (Frontiers in Medicine, 2019)
Background: Health-technology assessment (HTA) is a recognized mechanism to determine the relative benefits of innovative medical technologies. One aspect is their health-economic impact. While the process and methodology for pharmaceuticals is well established, guidance for medical devices is sparse. Aim: To provide an overview of the health-economic aspect in current European HTA guidelines concerning medical devices and identifying issues raised and potential improvements proposed in recent literature. Methodology: Available guidelines by European agencies were each reviewed and summarized. To complement this, a full systematic review of current literature concerning potential improvements to existing HTA practices for medical devices, from PubMed and EMBASE, was conducted; the focus was on health economics. Authors could only review documents in English, French, or German. The systematic review yielded 605 unique articles concerning HTA for medical devices, 32 of which were considered for full-text review after screening of all abstracts. Results: There is very limited consensus in—and mostly a complete lack of—guidance specific to medical devices in official HTA guidelines, for both clinical and economic analyses. 22 of 41 European countries had published official HTA guidance in English, French or German. Among these only 4 (England, France, the Netherlands, and Sweden) dedicated a chapter or separate document to medical devices. In the literature, there is sufficient evidence to suggest medical devices need to be addressed separately from pharmaceuticals. However, mostly challenges are discussed rather than implementable solutions offered. We present the following set of frequently discussed issues and summarize any solutions that pertain to them: a weak evidence base, learning-curve effects, organizational impact, incremental innovation, diversity of devices, dynamic pricing, and transferability. We further combine reviewed information to suggest a set of possible best practices for health-economic assessment of medical devices. Conclusion: For greater efficiency in medical-device innovation, European agencies should look to (re-)address the specific requirements of medical devices in their HTA guidelines. When both the health-economic and data requirements for the HTA of medical devices are defined, the development of practical solutions will likely follow.